A unique combination of coping strategies promotes each domain of post-traumatic growth during COVID-19: Differences between community residents and healthcare workers - Kalaitzaki, Argyroula; Tamiolaki, Alexandra; Tsouvelas, George (Psychology: the Journal of the Hellenic Psychological Society, 2024)
Undeniably the COVID-19 pandemic has resulted in unprecedented threats and severe traumas for human beings. However, for a proportion of people, the struggle with this crisis has led to positive mental health outcomes, known as posttraumatic growth (PTG). This study compared the PTG levels between community residents and healthcare workers (HCWs) across two time points and identified the coping strategies that promote each PTG domain separately. An online questionnaire was administered to 2,437 respondents (499 and 253 HCWs and 1157 and 528 community residents, at timepoints 1 and 2, respectively). The Post-Traumatic Growth Inventory assessed the five PTG domains and the Brief COPE the coping strategies. After controlling for gender, age, and education, ANCOVA showed a significant interaction effect; although HCWs had lower scores on PTG compared to community residents at T1, at T2 they had significantly higher scores. The coping strategies of positive reframing and religion positively predicted all PTG domains among both groups. Denial was the third most frequently used strategy, followed by active coping. On the other hand, certain coping strategies were unique predictors of specific PTG domains or groups. Self‒Distraction predicted community residents’ Personal Strength (also Behavioral Disengagement) and Appreciation of life, Emotional Support predicted community residents’ Relating to others and HCWs’ Appreciation of life, and self-blame predicted HCWs’ Relating to others and Personal Strength. The identification of these compilations of coping strategies for each PTG domain can guide preventive training programs targeting specific coping strategies that need to be enhanced in each sampling group.